The effects of electrode montage to the auditory brainstem response result - Dzulkarnain, Ahmad Aidil Arafat; Sulaiman, Nur Hafizah (2010)
Auditory Brainstem Response (ABR) is a complex response that represents neural activity from the VIIIth Cranial Nerve (CN) up to the brainstem level resulted from introduction of external stimuli. ABR can be recorded using several configurations such as vertical montage, horizontal montage, ipsilateral montage and contralateral montage. The purpose of this study is to investigate the effect of different electrode montage to the ABR results in three different intensities among 34 normal hearing subjects. The ABR was conducted to subject at 80, 50 and 30 dBnHL using rarefacting clicks for each of the electrode montages. In general, the descriptive and statistical analysis (Repeated measure ANOVA at 95% confident level) showed that the ABR waves were not 100% present across all the electrode montages and all electrode montages produced significantly different wave I, III and V amplitude, absolute latency and IPLs value at all intensity level. These findings were consistent with many previous literatures that were conducted at high stimulus levels. This study concluded that different electrode montages has its own advantages and limitations and therefore can be used for different clinical purposes.